Rice tungro spherical virus resistance into photoperiod-insensitive japonica rice by marker-assisted selection - Shim, Junghyun; Torollo, Gideon; Angeles-Shim, Rosalyn B; Cabunagan, Rogelio C; Choi, Il-Ryong; Yeo, Un-Sang; Ha, Woon-Goo (Breeding science, 2015)
Rice tungro disease (RTD) is one of the destructive and prevalent diseases in the tropical region. RTD is caused by Rice tungro spherical virus (RTSV) and Rice tungro bacilliform virus. Cultivation of japonica rice (Oryza sativa L. ssp japonica) in tropical Asia has often been restricted because most japonica cultivars are sensitive to short photoperiod, which is characteristic of tropical conditions. Japonica1, a rice variety bred for tropical conditions, is photoperiod-insensitive, has a high yield potential, but is susceptible to RTD and has poor grain quality. To transfer RTD resistance into Japonica1, we made two backcrosses (BC) and 8 three-way crosses (3-WC) among Japonica1 and RTSV-resistant cultivars. Among 8,876 BC1F2 and 3-WCF2 plants, 342 were selected for photoperiod-insensitivity and good grain quality. Photoperiod-insensitive progenies were evaluated for RTSV resistance by a bioassay and marker-assisted selection (MAS), and 22 BC1F7 and 3-WCF7 lines were selected based on the results of an observational yield trial. The results demonstrated that conventional selection for photoperiod-insensitivity and MAS for RTSV resistance can greatly facilitate the development of japonica rice that is suitable for cultivation in tropical Asia.